Assessment of carbon loss related to Soil loss in the tropical watershed of Maharashtra, India - Rahul Shelar; Sachin B. Nandgude; Atul A. Atre; Sunil D. Gorantiwar; Anil G. Durgude; Mahesh R. Patil (Environment Conservation Journal, 2023)
Soil carbon pools have a significant impact on the global carbon cycle and soil erosion caused by natural or human activities is one of the main drivers of changes in soil carbon sequestration. The present study aimed to estimate the carbon loss associated with soil loss in the watershed using remote sensing and GIS techniques. The study was carried out at the Central MPKV Campus Watershed, Rahuri, located in the rain shadow region of the Maharashtra state, India. The soil loss from the watershed was estimated using USLE model. The soil loss and carbon loss from the watershed were estimated before the implementation of conservation measures and after the implementation of conservation measures. It was found that the average annual soil loss from the watershed before and after conservation measures was 18.68 t/ha/yr and 9.41 t/ha/yr, respectively. Carbon loss was determined by soil loss rate, organic carbon content and the carbon enrichment ratio. The carbon loss from the watershed before and after conservation measures was 348.71 kgC/ha/yr and 205.52 kgC/ha/yr. The findings revealed that soil and carbon erosion was very severe on steep slopes without conservation measures and with limited vegetation cover. It was found that by reducing the carbon loss associated with soil loss, soil conservation measures not only aid in the conservation of natural resources but also serve as a climate change mitigation measure.